Oral terbinafine-, fluconazole-, ravuconazole-, oteseconazole-induced hepatotoxicity and acute kidney injury in the treatment of onychomycosis: a pharmacovigilance study - Rahman, Towsifur (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.